Barium M-Hexaferrite BaFe12O19 Based on Magnetic Properties and Microwafe Absorption - Noer Af'idah; Oktaffi Arinna Manasikan; Andri Wahyu Wijayadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Barium M-hexaferite is a material which has the potential to be developed as a magnetic material which is needed in various fields of application. Various methods have been used to produce this material, but in general these methods require heating at relatively high temperatures. This research was conducted to characterize the magnetic properties and microwave absorption of barium M-hexaferrite which was synthesized using the coprecipitation method by sintering at low temperatures. Synthesis of barium M-hexaferite was carried out using BaCO3, FeCl3. 6H2O, HCl, NH4OH. The results of the coprecipitation were dried using a light bulb at a temperature of 850C, then sintered at a 3000C with variations in holding times of 1 hour, 3 hours and 5 hours. The magnetic properties of the synthesized materials were tested using VSM, while the properties of microwave absorption were characterized using VNA. From the VSM test results, it can be determined that the highest remanence magnetization and coercivity values were found in the samples sintered at 3000C for 3 hours, namely Mr 0.103 emu/gram and Hc 0.058 Tesla. Meanwhile, from testing the absorption properties of the material for microwaves using VNA, it was found that the largest reflection loss value was found in the sample which was calcined for 3 hours, which was 52.4 dB or equivalent to an absorption of 99% at a frequency of 11 GHz. From the research it was found that barium M-hexaferite as a result of coprecipitation can be developed into a good microwave absorbent material.